2012
DOI: 10.1016/j.jtcvs.2011.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of using solid versus whole tumor size on high-resolution computed tomography for predicting pathologic malignant grade of tumors in clinical stage IA lung adenocarcinoma: A multicenter study

Abstract: The solid tumor size on high-resolution computed tomography and maximum standardized uptake values on positron emission tomography/computed tomography have greater predictive value for high-grade malignancy and prognosis in clinical stage IA lung adenocarcinoma than that of whole tumor size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
134
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(146 citation statements)
references
References 20 publications
9
134
3
Order By: Relevance
“…Several reports [9][10][11][12][13] have described patients with similarly defined lung MIA and a disease-specific survival rate of nearly 100%. Furthermore, some reports 14,15) have demonstrated that tumor malignancy depends on the maximum diameter or area of its solid component, excluding the ground-glass opacity (GGO) component. Correlations between tumor malignancy and MRI and PET findings have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports [9][10][11][12][13] have described patients with similarly defined lung MIA and a disease-specific survival rate of nearly 100%. Furthermore, some reports 14,15) have demonstrated that tumor malignancy depends on the maximum diameter or area of its solid component, excluding the ground-glass opacity (GGO) component. Correlations between tumor malignancy and MRI and PET findings have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that these radiological evaluations can be subjective and can affect the outcomes of such studies directly. Our main concern is that radiological evaluations may result in discrepancies in outcomes among studies, including those of this study (1)(2)(3)5 (8). Therefore, the median follow-up time used by Hattori et al was too short to confirm their conclusion regarding the importance of the GGO component as a significant clinical T descriptor.…”
mentioning
confidence: 73%
“…Tsutani et al (6) demonstrated that solid tumor size has a greater predictive value for prognosis in clinical stage IA lung adenocarcinoma than that of whole tumor size. Their study (6) analyzed whole tumor types including pure GGO, part-solid, and solid nodules. Hattori's study (4) is impressive and interesting in terms of the fact that they found that evaluation of the maximum tumor size should be applied only to a solid tumor without GGO, and not to either a pure GGO or a part-solid tumor.…”
Section: Commentarymentioning
confidence: 99%